Nodal histiocytic disorder in children: report of three cases and review of literature - Ainer, Indumathi; Gendeh, Hardip Singh; Husain, Salina; Mohd Nor, Khadijah (Springer, 2020)
Background: Histiocytic system consists of phagocytes and dendritic cells. Both are found in lymph nodes. Usually, this disorder presents with painless cervical lymph node enlargement hence frequently mistaken for lymphoma or tuberculosis. Case presentation: Here, we report three pediatric cases: one of Langerhans cell histiocytosis and two of sinus histiocytosis and massive lymphadenopathy with neck mass as initial presentation. The final diagnosis was made with fine needle aspiration cytology, biopsy, and ancillary tests. Conclusion: Biopsy and immunohistochemistry studies are recommended for determining subtypes of histiocytosis and further management of patient.